Visualisation of nanoslurries and hybrid nanomaterials - Kadhim, Manahil (2019)
The use of nanomaterials has become increasingly important in the past 50 years in applications such as transport, health and catalysis. Prior to usage either individually or in combination with polymers, these nanomaterials must be tested for quality, such as stability, or for different properties ¬ such as total refractive index (RI), concentration and solubility in different solvents. Traditional techniques, such as transmission electron microscopy (TEM), can be expensive and time-intensive. A novel and low-cost technique involving the use of a digital camera (Logitech HD Pro C920), an iPad (Apple) and a computer to characterise the aforementioned properties of nanomaterials has been developed. The images were taken in clear glass cuvettes against different background colours (red, blue and green) and patterns (striped, lettered and dotted). This was done to reveals variations in the RI, colour intensity, concentration and settling rates after processing of images using MATLAB. Results indicated that, in the case of Fe2O3 (iron (III) oxide) nanoparticles prepared at temperatures ranging 200-400°C, accurate settling rates were obtained and quantified during 5 h. This was evidenced by an increase in the mean pixel value (which represents the degree of settling) after 5 h for samples formulated at 300°C and above. Similarly, the RI values increased in correlation with the concentration of sucrose in the solution and was evidenced by an increase in the quantified letter areas. Furthermore, a high initial pixel value of the red channel was obtained before decreasing in correlation with an increase in Nigrosin blue dye concentration (in ppm) exhibiting sensitivity to concentration. Conversely, the blue channel value revealed the reverse trend. In conclusion, an accessible, simple and cost-effective system has been developed to calculate multiple properties of different types of solutions.